(untitled) (Revista de Artes Marciales Asiáticas, 2025)
This study investigated physiological and perceptual responses between uke (the athlete receiving a technique) and tori (the athlete executing a technique) during intermittent osaekomi-waza exercises in prepubescent judo athletes. Fifteen child judo athletes (age: 10.8 ± 1.1 years) participated voluntarily. In this cross-over design with randomization (except for the first visit), athletes completed three sessions: anthropometric measurements and familiarization, followed by intermittent osaekomi-waza exercises as both uke and tori. The exercise protocol consisted of four sets of 20-second intermittent osaekomi-waza using kesa-gatame, interspersed with 10-second rest intervals (1:½ work-to-rest ratio), performed on separate days. Heart rate (HR) was measured at rest, immediately after exercise, and one minute after exercise. The rating of perceived exertion (RPE) was assessed using a 0–10 scale immediately after each exercise bout. While a two-way repeated measures ANOVA indicated a statistically significant main effect of role on HR, with higher values in the uke role compared to the tori role across all measurement times, Bayesian analysis did not provide substantial evidence supporting this role effect. Athletes also reported significantly higher RPE scores in the uke role than in the tori role, indicating greater perceptual demands in prepubescent judo athletes, despite similar heart rate patterns between roles.